Evaluating the transitional mosaic: frameworks of change from Neanderthals to Homo sapiens in eastern Europe. (15th June 2015) - Davies, William; White, Dustin; Lewis, Mark; Stringer, Chris
Abstract: Defining varying spatial and temporal analytical scales is essential before evaluating the responses of late Neanderthals and early Homo sapiens to Abrupt Environmental Transitions (AETs) and environmental disasters for the period 130–25 ka. Recent advances in addressing the population histories and interactions (using both genetic and archaeological evidence) of Neanderthals and H. sapiens have encouraged consideration of more subtle dynamics of archaeological change. Descriptions of change based on methodologies pioneered some 160 years ago are no longer adequate to explain the patterning we now see in the record. New chronological results, using multiple dating methods, allow us to begin to unpick the spatial and temporal scales of change. Isochronic markers (such as specific volcanic eruptions) can be used to create temporal frameworks (lattices), and results from other dating techniques compared against them. A combination of chronological lattices and direct dating of diagnostic artefacts and human fossils permits us, for the first time, to have greater confidence in connecting human (recent hominin) species and their behavioural responses to environmental conditions, and in quantifying scales of change over time and space (time-transgression). The timing of innovations, particularly those in bone, antler and ivory, can be directly quantified and tested, and used to re-evaluate longstanding models of cultural change. This paper also uses these new chronologies to explore the ecologies of late Neanderthals and early H. sapiens : their population densities, mobilities, resources exploited and possible interactions. Environmental productivity estimates are used to generate new questions of potential population densities and mobilities, and thus the sensitivity of these groups to environmental perturbations. Scales and intensities of effect on environments from natural disasters and AETs (notably Heinrich Events and the Campanian Ignimbrite eruption) are defined as a scale from "proximal" to "distal, " with local conditions (topographic shelter or exposure) serving to intensify or mitigate those effects. Highlights: We use volcanic ash shards to test new timescales for Neanderthals and Homo sapiens . We model ancient human population responses to sudden environmental changes. New models of Neanderthal and H. sapiens ecology are evaluated in detail. Neanderthal extinction cannot be directly attributed to rapid environmental change. Dated bone projectile innovations were not triggered by rapid environmental change.